Effects of night shift work towards health and safety of production workers - BM Deros,; NK Khamis,; AR Ismail,; A Ludin, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Introduction : Shift work is practised in manufacturing industry to increase production capacity up to three times compared to the normal daily eight hours working system and able to optimize the utilization of machine and equipment. However, shift work has negatif effects on human social interaction, health and safety. Methodology : The study was conducted to evaluate production workers’ perception on the effects of working at night shift. The respondents of the study were production workers in Company X in Kuala Lumpur. The Data was collected using self administered questionnaires. The study objectives was to study the work schedule design, to find out their perceptions on the effects of night shift and to study on personal factors, employees’ level of acceptance on the work schedule design and personal factors that cause safety and health disruption. Result : A total of 200 production workers participated in the study. The result of the study shows 61% of production workers took sick leave and 43.5% were absent between 1 and 2 times a month. In terms of health and safety disruption, 77% of respondents agreed that they faced lack of focus with family and friends, 75.5% of them did not have enough sleep and 76.5% felt sleepy during working time. Regarding the work schedule and workstation design, 81.5% said they felt uncomfortable because they were required to stand during working and 77% felt that the resting period provided by the factory was too short and inadequate. More than 70% of the respondents proposed the rest period should be extended from the current 40 minutes to one hour. More than 80% of respondents agreed they would feel comfortable if standing at work is changed to sitting work system. Conclusion : To minimize the unwanted effect of night shift among the production workers, the company Should evaluate the present working schedule and work station design.